The Identification of Language Functions and Expressions Used by Gift Shop Attendants in Lovina Bali Resort - Jessica Agnes Aprinita; Putu Suarcaya; Ni Putu Era Marsakawati (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study entitled Identification of Language Functions and Expressions used by Gift Shop Attendants in Lovina Bali Resort. The purpose of this study is to know how Gift Shop attendants use their skills in communicating with customers during shopping. It also concerns to the utilize of the language functions and expressions used in various context of discourse. In identifying those language functions and expressions, the researcher involving Language Function Theory that is developed by Blundell (1987), Meta Function Theory (Halliday, 1994), as well as some of theories that relevant to this study. The researcher is using descriptive qualitative approach to collect the data in the form of words related to language functions and expressions. Data collection is done through observation and recording the interaction of Gift Shop attendant while serving the customers in various aspect of shopping experience. In this study, the researcher gets 2 Gift Shop attendants as subject of study, and after all data were collected and analysed, as the result obtained there are 9 language functions used by Gift Shop attendants in Lovina Bali Resort, that are; describing product, telling for the price, informing availability, greeting customers, offering assistance, suggesting product, requesting payment, thanking the customers, and structuring conversation. The Gift Shop attendants in Lovina Bali Resort mostly applied interpersonal function of language, as well as using directive expression when interacting with the customers.